2018
DOI: 10.3390/stats2010001
|View full text |Cite
|
Sign up to set email alerts
|

Cronbach’s Alpha under Insufficient Effort Responding: An Analytic Approach

Abstract: Surveys commonly suffer from insufficient effort responding (IER). If not accounted for, IER can cause biases and lead to false conclusions. In particular, Cronbach's alpha has been empirically observed to either deflate or inflate due to IER. This paper will elucidate how IER impacts Cronbach's alpha in a variety of situations. Previous results concerning internal consistency under mixture models are extended to obtain a characterization of Cronbach's alpha in terms of item validities, average variances, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…A comparable pattern has been reported in another longitudinal study recruiting depressed patients [ 32 ]. In terms of theoretical mechanisms, it is possible that there is an interplay between psychopathological symptomology and the properties of internal consistency reliability: it has been shown that reliability of a self-report Likert scale may be affected by “insufficient effort responding” (careless responding styles), for example by “straightlining” identical responses or giving random ratings [ 37 ], resulting in biased estimates of internal consistency [ 38 ]. Accordingly, recent research has shown that psychiatric symptoms are associated with less consistent response patterns on self-rated scales [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A comparable pattern has been reported in another longitudinal study recruiting depressed patients [ 32 ]. In terms of theoretical mechanisms, it is possible that there is an interplay between psychopathological symptomology and the properties of internal consistency reliability: it has been shown that reliability of a self-report Likert scale may be affected by “insufficient effort responding” (careless responding styles), for example by “straightlining” identical responses or giving random ratings [ 37 ], resulting in biased estimates of internal consistency [ 38 ]. Accordingly, recent research has shown that psychiatric symptoms are associated with less consistent response patterns on self-rated scales [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Once the validation process was completed, the reliability of the questionnaire was analyzed. For this, a global statistical analysis and an individual item analysis for each item were carried out using Cronbach's alpha; once these analyses were completed, the Spearman-Brown and Guttmann coefficients were used as complementary tests [59].…”
Section: Methodsmentioning
confidence: 99%
“…With a view to validating the research constructs prior to structural equation modeling, Carden et al (2019) recommend the need to conduct validity testing of the extracted dimensions. For the construct validity, the researcher considered the use of the Confirmatory Factor Analysis (CFA) as prescribed by Tabachnick and Fidell (2007) and affirmed by Hair et al (2018).…”
Section: Construct Validationmentioning
confidence: 99%
“…Moreso, according to Field (2016) together with Carden et al (2019), the general standard threshold for the assessment of reliability is 0.7, however, alpha loadings as low as 0.6 are still considered to be reliable while those above 0.7 are considered to be the most desirable (Sweet & Grace-Martin, 2012). From the above results, the least observed alpha statistic was 0.350 for the sixth component and this was less than 0.70, while the second least was the fifth component (0.497), again, less than 0.70.…”
Section: Rotated Component Matrixmentioning
confidence: 99%